Hepatopulmonary syndrome after radiofrequency ablation of recurrent intrahepatic cholangiocarcinoma: a case report - Wang, Yu; Ma, Kuansheng; Zhong, Ai; Xiong, Qing; Chen, Jian (OncoTargets and therapy, 2019)
Radiofrequency ablation (RFA) is one of the definitive treatment modalities for liver cancer and has been increasingly used in the scenario of small-sized liver cancer. It is generally believed that RFA is minimally invasive and associated with a favorable safety profile in liver cancer patients. However, this interventional technique is subject to some morbidity in high-risk patients, such as those with complicating cirrhosis or a liver cancer located at a refractory segment. Herein, we report the case of a middle-aged woman who developed acute liver failure with a complicating respiratory failure after RFA of recurrent intrahepatic cholangiocarcinoma. A diagnosis of hepatopulmonary syndrome was established. The patient was hospitalized in the intensive care unit for mechanical ventilation. Finally, the patient recovered from an eventful clinical course and survived free of recurrence until the last follow-up visit at 1 year after the discharge. Our case report warns that hepatopulmonary syndrome, a less common morbidity secondary to liver cancer RFA, should require timely identification and appropriate management due to its life-threatening outcome.